Correlation between infection by ophiostomatoid fungi and the presence of subterranean termites in loblolly pine (Pinus taeda L.) roots - Riggins, John J.; Little †, Nathan S; Eckhardt, Lori G. (published online, 2014)
1 Observations of subterranean termites feeding in pine sapwood containing ophiostomatoid fungi prompted the present study aiming to investigate the effect of infection by Leptographium fungi on the probability of encountering subterranean termites in loblolly pine (Pinus taeda L.) roots. 2 Root samples were collected from 2350 loblolly pine trees in Alabama, Texas, Louisiana and Mississippi using hand tools. The presence or absence of subterranean termites in the roots was recorded. Samples were plated on malt extract agar and cycloheximide-streptomycin malt agar and incubated to determine which, if any, fungal species were present. 3 The presence of Leptographium procerum, Leptographium terebrantis or both was significantly associated with an increased presence of subterranean termites in loblolly pine roots. 4 The results obtained in the present study indicate that complex ecological interactions may exist between ophiostomatoid fungi, as carried by root-feeding bark beetles, and subterranean termites.
Full text
Keywords: Blue-stain fungi, Leptographium, loblolly pine roots, ophiostomatoid, Pinus taeda L., subterranean termites.